Infantile Epithelioid Sarcoma with Genomic Segmental Amplification of BIRC3/YAP1 as Double Minutes Plus Trisomy 2: A Case Report. (2nd January 2020) - Srinivasan, Anand; Liu, Meng; Parham, David; Li, Ming; Wang, Xianfu; Lu, Xianglan; Li, Shibo; Zhang, Lijun; Yu, Zhongxin
Abstract: Introduction: Epithelioid sarcoma is a malignant mesenchymal tumor exhibiting epithelioid cytomorphology and epithelial phenotype. Its histogenesis is unknown, but its tumorigenesis may relate to inactivation of hSNF5/SMARCB1/INI1 tumor suppressor gene. This tumor typically affects young adults and older children, but it is uncommon in infants. Case Report: We describe a unique neoplasm in a 15-month-old infant presenting with a heel mass. The tumor was remarkable for retention of SMARCB1/INI1 expression. Conventional cytogenetic analysis revealed trisomy 2 and double minutes, and SNP array analysis confirmed the trisomy 2 and identified segmental amplification of chromosome 11 containing YAP1 and BIRC3 ; FISH testing proved that the double minutes consisted of BIRC3 and YAP1, potent oncogenes related to tumorigenesis of several types of tumors but not described in epithelioid sarcoma. Conclusion: Our findings expand the spectrum of cytogenetic alterations in this neoplasm, help in better understanding its tumorigenesis, and suggest potential therapeutic targets.